Pengembangan Media Pembelajaran Augmented Reality Untuk Meningkatkan Pemahaman Konsep IPA Di Sekolah Dasar - Ahmad Nazwan; Zamroni Hidayat; Aprian Akbar (PGSD UNU NTB, 2025)
This study aims to develop an Augmented Reality (AR)-based learning media to improve elementary school students’ understanding of science concepts. The development follows the ADDIE model, which includes the stages of analysis, design, development, implementation, and evaluation. The analysis stage identifies students’ difficulties in understanding abstract science concepts. The design stage emphasizes three-dimensional object visualization and interactivity. In the development stage, the AR media is integrated with learning modules that enable students to explore topics such as organ systems, natural cycles, and environmental phenomena through interactive features. Expert validation results indicate a high level of feasibility, with scores above 85% in terms of content relevance, display clarity, ease of use, and interactivity quality. Classroom implementation shows a significant improvement in learning outcomes based on pre-test and post-test comparisons, as well as an N-Gain score above 0.70. Students’ responses are highly positive, as reflected in their enthusiasm, engagement, and strong learning motivation. The AR-based media is effective in facilitating conceptual understanding, critical thinking, and the ability to relate learning materials to real-life phenomena, while also supporting interactive, contextual, and innovative learning in the digital era.